Change in Function, Pain, and Quality of Life following Structured Nonoperative Treatment in Patients with Degenerative Cervical Myelopathy: A Systematic Review. Issue 1 (April 2016) - Tetreault, Lindsay; Shamji, Mohammed; Rhee, John; Wilson, Jefferson; Anderson, Ian; Dembek, Anna; Pagarigan, Krystle; Dettori, Joseph; Fehlings, Michael
Introduction: The role of structured nonoperative treatment for the management of DCM is not well defined, and surgery is typically recommended as the default treatment option for patients with moderate and severe myelopathy. This study aims to conduct a systematic review of the literature to determine (1) the change in function, pain and quality of life following structured nonoperative treatment for degenerative cervical myelopathy (DCM); (2) the variability of change in function, pain and quality of life following different types of structured nonoperative treatment; (3) the differences in outcomes observed between certain subgroups (i.e baseline severity score, duration of symptoms); and (4) negative outcomes and harms resulting from structured nonoperative treatment. Material and Methods: A systematic search was conducted in Embase, PubMed, and the Cochrane Collaboration for articles published between January 1, 1950 and February 9, 2015. Studies were included if they evaluated outcomes following structured nonoperative treatment, including therapeutic exercise, manual therapy, cervical bracing and/or traction. Outcomes of interest were functional status (Japanese Orthopedic Association (JOA), Nurick), pain in upper extremities and neck, quality of life (Neck Disability Index), and/or conversion to surgery. The quality of each study was evaluated using the Newcaste-Ottawa Scale and the strength of the overall body of evidence was rated using guidelines outlined by the Grading of Recommendation Assessment, Development and Evaluation Working Group. Results: Of the 570 retrieved citations, eight met the inclusion criteria and were included in this review. There is very low evidence to suggest that structured nonoperative treatment for DCM results in a positive or negative change in function, pain and quality of life as evaluated by the JOA score. There is also limited evidence from three studies indicating that early structured nonoperative treatment (duration of symptoms < 1 year) may be associated with positive clinical outcomes. There were no studies that directly compared structured nonoperative treatment types and no studies that explored outcomes based on patient subgroups. The rate of conversion to surgery was reported to be between 23-54% in mostly cases of mild or moderate myelopathy (JOA≥12). Conclusion: There is a lack of evidence to determine the role of nonoperative treatment in patients with DCM. However, in the majority of studies, patients did not achieve clinically significant gains in functional status following structured nonoperative treatment. Furthermore, rates of failed conservative treatment were between 23-54%.